Temporal Modulation of the Local Microseism in the North Sea. Issue 10 (30th September 2020) - Becker, D.; Cristiano, L.; Peikert, J.; Kruse, T.; Dethof, F.; Hadziioannou, C.; Meier, T.
Abstract: Primary and secondary microseism originating in the world oceans and peaking at around 14 and 7 s, respectively, characterize the Earth's background noise in that frequency range. Microseism generated in marginal seas with partly shorter periods and higher spatial and temporal variability is less studied and requires stations in immediate proximity to the source to be observed. Such studies can help to elucidate the exact microseism generation areas and mechanisms in a constrained area. We analyze 15 years of broadband data recorded at the seismic station on Helgoland island in the marginal North Sea. In addition to remote primary (RPM) and secondary microseism (RSM) originating in the North Atlantic, we observe strong and dominant local secondary microseism (LSM) with on average higher frequencies above 0.2 Hz, in accordance with shorter wave periods of about 4–8 s in the shallow North Sea. During times with low RSM activity we observe local primary microseism (LPM) at frequencies in agreement with local ocean wave periods. The higher horizontal to vertical (H/V) ratio of LPM with respect to LSM indicates a major non‐Rayleigh wave contribution. LSM and LPM show a strong modulation with local semidiurnal ocean tides and microseism energy maxima preceding the water level maximum by 2.5 and 1.5 hr, respectively. This time shift might be influenced by stronger currents during rising than falling tides. Active sources of tide‐modulated microseism migrate along the North Sea coast in sync with the ocean tidal signal as evidenced by comparison of LSM maxima at stations distributed along the coast. Key Points: At an island in the marginal North Sea, we observe strong local primary and secondary microseism at shorter periods than remote microseism Local microseism exhibits a strong tidal modulation and high horizontal to vertical (H/V) ratios in the primary microseism signal The source region of the tidal‐modulated local microseism seems to migrate in sync with the progression of the ocean tides Plain Language Summary: Ocean sea waves cause seismic waves in the solid earth. These seismic waves have either the same period or half that period. They are caused by interaction of water waves with shallow seafloor structures or the interference of waves with equal period and opposite propagation directions, respectively. The period of ocean waves depends, among other factors, on the size of the water body. A smaller water body causes shorter wave periods. At an island station in the North Sea, a marginal sea of the North Atlantic, we observe simultaneously seismic wave energy generated nearby in the North Sea and far away in the North Atlantic. The North Atlantic in general generates seismic waves with longer periods. We observe seismic waves with the period and half the period of water waves in the North Sea. In addition, a modulation of the locally generated seismic wave energy with ocean tides is observed. The sources of this tidal‐modulated energy move with the tidal front. This is interesting, as the exact conditions necessary to generate these seismic waves are not well understood. Our station location in direct vicinity to the generation area allows for the novel observations presented here.